Correlation of pre-operating antibiotic types with surgical site infection in post-appendectomy patients - Romadoni, Fitria; ., Handayani; Bhayusakti, Aditya (Gaceta Médica de Caracas, 2021)
Introduction: Prophylactic antibiotics are antibiotics given to patients undergoing surgery to prevent infection due to surgery. Surgical site infection (SSI) is an infection that occurs when microorganisms from the skin, other body parts, or the environment enter the postoperative incision. This study aimed to analyze the relationship between preoperative antibiotics and the occurrence of SSI.